2001
DOI: 10.1002/cne.1302
|View full text |Cite
|
Sign up to set email alerts
|

Connections of higher order visual relays in the thalamus: A study of corticothalamic pathways in cats

Abstract: Axonal markers injected into layers 5 and 6 of cortical areas 17, 18, or 19 labeled axons going to the lateral geniculate nucleus (LGN), the lateral part of the lateralis posterior nucleus (LPl), and pulvinar (P). Area 19 sends fine axons (type 1, Guillery [1966] J Comp Neurol 128:21-50) to LGN, LPl, and P, and thicker, type 2 axons to LPl and P. Areas 17 and 18 send type 1 axons to LGN, and a few type 1, but mainly type 2 axons to LPl and P. Type 1 and 2 axons from a single small cortical locus distribute to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
68
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 52 publications
7
68
0
1
Order By: Relevance
“…Alternatively, the visual activity in the LPl that remains when area 17 is silenced may be contributed by projections from areas 18, 19, or 21a. These areas all innervate the LPl (Updyke, 1977(Updyke, , 1986Berson and Graybiel, 1983), and the projections from areas 18 and 19 have been shown to exhibit type II morphology (Ojima et al, 1996;Guillery et al, 2001). In addition, the LPl receives direct input from the retina (Boire et al, 2004).…”
Section: Evidence For the Integration Of Cortical Inputs In The Lplmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the visual activity in the LPl that remains when area 17 is silenced may be contributed by projections from areas 18, 19, or 21a. These areas all innervate the LPl (Updyke, 1977(Updyke, , 1986Berson and Graybiel, 1983), and the projections from areas 18 and 19 have been shown to exhibit type II morphology (Ojima et al, 1996;Guillery et al, 2001). In addition, the LPl receives direct input from the retina (Boire et al, 2004).…”
Section: Evidence For the Integration Of Cortical Inputs In The Lplmentioning
confidence: 99%
“…2B-D). In the nomenclature of Guillery et al (2001), these terminals were classified as singletons. Two larger terminal types formed more complex endings.…”
Section: Classification Of Area Pmls Corticothalamic Terminal Morphologymentioning
confidence: 99%
“…It has been suggested recently that the cortex may provide the primary or driving input to higher order nuclei, such as the PUL and lateral posterior nucleus (LP; Guillery, 1995;Guillery et al, 2001). This is based on the observation that terminals in the LP originating from layer V of the striate cortex are similar in morphology (RL profiles, denoting large terminals that contain round vesicles) to retinal terminals in the dorsal lateral geniculate nucleus (dLGN; Vidnyánszky et al, 1996;Feig and Harting, 1998).…”
Section: Indexing Termsmentioning
confidence: 99%
“…Neurons located in this region were originally described as polysensory (Amassian, 1954); although later studies indicated that neurons within this region could be categorized primarily based on their responses to visual stimuli, including stationary spots, brisk movements, and oriented edges (Thompson et al, 1963; Dubner, 1969, 1971;Robertson et al, 1975; Yin and Greenwood, 1992a,b). More recently, visual, saccade, and fixational responses were distinguished within more caudal portions of the MSg (Yin and Greenwood, 1992b).It has been suggested recently that the cortex may provide the primary or driving input to higher order nuclei, such as the PUL and lateral posterior nucleus (LP; Guillery, 1995;Guillery et al, 2001). This is based on the observation that terminals in the LP originating from layer V of the striate cortex are similar in morphology (RL profiles, denoting large terminals that contain round vesicles) to retinal terminals in the dorsal lateral geniculate nucleus (dLGN; Vidnyánszky et al, 1996;Feig and Harting, 1998).…”
mentioning
confidence: 99%
“…Examples of these higher order relays are the pulvinar for vision, the posterior nucleus for somesthesia, and the magnocellular portion of the medial geniculate nucleus for hearing (Sherman andGuillery, 1996, 2006;Sherman, 2005). Central to this view is evidence showing that synaptic properties of corticothalamic input from layer 5 to higher order nuclei share the same driver properties measured anatomically, physiologically, and pharmacologically as do retinogeniculate input and medial lemniscal input to the ventral posterior nucleus (Schwartz et al, 1991;Hoogland et al, 1991;Deschênes et al, 1994;Ojima, 1994;Rockland, 1996;Rouiller and Welker, 2000;Bartlett et al, 2000;Guillery et al, 2001;Li et al, 2003b;Reichova and Sherman, 2004). These higher order relays have only been recently recognized, and they seem to occupy the majority of thalamus (Sherman and Guillery, 2006).…”
mentioning
confidence: 98%